Penguatan Infrastruktur Digital Desa Melalui Penerapan Jaringan RT/RW-Net Di Desa Neglasari, Sumedang - Carudin Carudin; Joni Warta; Asep Ramdhani Mahbub; Agus Hidayat (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2026)
Neglasari Village, Darmaraja District, Sumedang Regency, needs a more structured local network to support village administration, information delivery, public access, coordination activities, and local economic services. This community service activity aimed to strengthen village digital infrastructure through the implementation of an RT/RW-Net network. The activity was carried out using a participatory approach through observation, needs mapping, network topology design, device installation and configuration, user training, and initial evaluation. The network architecture was designed by connecting the internet source, modem/ONT, router gateway, distribution device, access points, and users at priority service areas. Training was also provided to village officers and users to improve their understanding of network utilization, access ethics, password security, and basic troubleshooting. The initial results show that the RT/RW-Net network provided a more structured connectivity foundation for village digital services. In addition, participants gained basic knowledge of network use and maintenance, enabling the village to manage simple connectivity issues more independently. This program supports the gradual and sustainable development of digital village services in Neglasari Village.